PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Devi Lindaratri Yulianti, 14.05.51.0193; Rahayuningsih, Sri (Students' Journal of Economic and Management, 2018)
This study analyze about the influence of leadership styles transformational, competence and compensation toward the performance of the nurse. The research object in this research is nurse of Sultan Agung Islamic Hospital Semarang. The sampling technique used in this research is purposive sampling. Data collection techniques used in this study is distributing questionnaires directly to the nurse of Sultan Agung Islamic Hospital Semarang. The purpose of the study was formulated to determine the effect of leadership styles transformational, competence and compensation toward the performance of the nurse at the Islamic Hospital Sultan Agung Semarang. The data collected were analyzed using factor analysis that test the KMO and loading factor to test the validity of the item indicators of the statement, the formula of cronbach alpha to test the reliability of each variable was tested with multiple linear regression analysis. As for the results of the study as follows : (1) The Style of Transformational Leadership have positive and significant influences on the performance of the nurse; (2) Competence has positive and significant influence on the performance of the nurse; (3) Compensation have positive and significant influences on the performance of nurses. Keywords : Leadership Style Transformational, Competence, Compensation and Performance of Nurses.